2021
DOI: 10.13057/biodiv/d220524
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Morphometric variations in two populations of Limnophora marginata Stein, 1904 (Diptera, Muscidae) in Ecuador

Abstract: Abstract. Ruiz MA, Acosta-López C, Soto-Vivas A. 2021. Short Communication: Morphometric variations in two populations of Limnophora marginata Stein, 1904 (Diptera, Muscidae) in Ecuador. Biodiversitas 22: 2654-2657. Limnophora includes 230 species, eleven of which are present in Ecuador. There are few studies on the bioecology of these species in the country. However, recent studies indicate that Limnophora marginata Stein, 1904 as the most abundant species in the Evergreen High Montane Forest (EHMF) located a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These aspects correspond to the results found in this investigation, since the altitudinal gradient did not influence the interpopulation genetic variability. Our parallel project analyzing morphological differences with geometric morphometric tools (Ruiz et al 2021) concluded that the found diversity was probably due to the plasticity of the species. Encompassing such analyses with molecular markers results in a more comprehensive view of the populations dynamics and allows us to better understand changes in population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These aspects correspond to the results found in this investigation, since the altitudinal gradient did not influence the interpopulation genetic variability. Our parallel project analyzing morphological differences with geometric morphometric tools (Ruiz et al 2021) concluded that the found diversity was probably due to the plasticity of the species. Encompassing such analyses with molecular markers results in a more comprehensive view of the populations dynamics and allows us to better understand changes in population.…”
Section: Resultsmentioning
confidence: 99%
“…The population of this study includes 526 L. marginata individuals for the Tocachi parish in Evergreen High Montane Forest (-78.290500 W 0.048400 N) and 32 for the Malchingui parish in Dry Forest (-78.358324 W-0.000693 S), located at the Pedro Moncayo Canton of the Pichincha Province, Ecuador (Figure 1). Samples were collected through necrotraps as established in Ruiz et al (2021). The sample was selected in coordination with the parallel morphogeometrics project (Ruiz et al 2021).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The Coenosiinae subfamily is widespread in the Neotropical region, characterized by aquatic larvae, which included Limnophoriini and Coenosiini, most species for Limnophoriini are found in humid or dry environments, also it currently includes only 12 genders (Alves et al, 2016) The genus Limnophora includes approximately 230 species spread in different habitats. They live in high and dry forests and can be found from high mountains to valleys, rivers, and streams (Ruiz et al, 2021). Coenosiinae is one of the subfamilies belonging to the family Muscidae, and the common name of its family members is hunter flies or killer flies (de Jong et al, 2014; Martinez & Cocquempot, 2000).…”
Section: Introductionmentioning
confidence: 99%